The Mediating Role of Depressive Symptoms, Hopelessness, and Perceived Burden on the Association Between Pain Intensity and Late-Life Suicide in Rural China: A Case–Control Psychological Autopsy Study - Wang, Jiali; Xu, Jiahuan; Ma, Zhenyu; Jia, Cunxian; Wang, Guojun; Zhou, Liang (Frontiers in Psychiatry, 2021)
Background: Few studies have investigated the roles of psychosocial factors such as depressive symptoms and hopelessness on the relationship between pain and suicide with inconsistent results. The study aimed to analyze the impact of pain intensity on suicide death and to estimate the degree to which depressive symptoms, hopelessness, and perceived burden may explain the association in Chinese rural elderly. Methods: Using a 1: 1 matched case-control design, we collected data from 242 elderly suicide cases and 242 living community controls by psychological autopsy method in rural China, including sociodemographic characteristics, pain intensity, depression, hopelessness, perceived burden, physical diseases, and social support. Conditional logistic regression was employed to assess the association between pain intensity and completed suicide. Mediation analysis using the KHB method was applied to explore the mediation effects from depressive symptoms, hopelessness, and perceived burden. Results: The result of multivariable logistic regression showed that unemployment (odds ratio (OR) =5.06, 95% confidential interval (CI): 1.76- 14.49), higher levels of hopelessness (OR=7.72, 95% CI: 3.49- 17.10), depressive symptom (OR=15.82, 95% CI: 4.53- 55.25), and severe pain (OR=3.46, 95% CI: 1.31- 9.13) were significantly associated with elevated suicide risk in older adults in rural China. Depressive symptoms, hopelessness, and perceived burden significantly mediated 43.71% of the pain-suicide association (P = 0.020), with 17.39% due to depressive symptoms, 17.63% due to hopelessness, and 8.69% due to perceived burden. Conclusions: Regular screening of pain, depressive symptoms, hopelessness, and perceived burden using simple but sensitive questions or scales for older adults with pain are vital for the prevention and early detection of suicide risk in Chinese rural areas. Moreover, the importance of pain management and psychological interventions targeted on depressive symptoms and hopelessness should be emphasized.